Private pension schemes. Their role in adequate and sustainable pensions (Luxembourg, 2010)
"Reforms to pension systems have been ongoing. Member States are facing the challenge of population ageing which is putting a significant strain on current pension systems. This brochure examines the growing importance of privately managed funded pension schemes."